2022
DOI: 10.1007/s10461-022-03933-w
|View full text |Cite
|
Sign up to set email alerts
|

Global Online Interest in HIV/AIDS care Services in the time of COVID-19: A Google Trends Analysis

Abstract: The Covid-19 pandemic has compounded the challenge of HIV/AIDS elimination, creating difficulties in accessing HIV care services such as early testing and treatment. This paper characterized the global online interest in HIV care services-related search terms before and during the pandemic. Global online search interest for HIV was measured using the Google Trends™ database. Spearman’s rank-order correlation correlated country-specific characteristics and HIV prevalence data with the search volume index (SVI).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…The infoveillance approach used was Google Trends database, whereas the SCOPUS database was used for the bibliometric analysis. These two databases have been extensively used in the literature [10][11][12][13][14][15].…”
Section: Databasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The infoveillance approach used was Google Trends database, whereas the SCOPUS database was used for the bibliometric analysis. These two databases have been extensively used in the literature [10][11][12][13][14][15].…”
Section: Databasesmentioning
confidence: 99%
“…Asides Google Trends search database, there are other online search databases that can be used for infoveillance studies; however, Google Trends is the most preferred database because it is the oldest one and it has broader global coverage, usage and comprehensiveness compared to other databases [10,11]. Additionally, the analysis of infoveillance data obtained from Google Trends provides insightful information on public interests; it also explores the epidemiological features and dynamic variations in infectious diseases such as COVID-19 [10,14,15]. Hence, the above justifies the use of Google Trends for this study.…”
Section: Databasesmentioning
confidence: 99%
“…In this study, interest in HIV self-testing has remained relatively high during the COVID-19 pandemic. Even though web-based search interest only indicates clinical information-seeking behavior, recent infodemiology studies, including that by Ornos et al [15], showed that search volume indices correlated positively with HIV prevalence and negatively with financial and health care service status. Another recent study in Japan by Ishimaru et al [30] also observed a positive correlation between internet search frequency for HIV/AIDS-related terms and the number of voluntary tests.…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 pandemic, infodemiology studies found that web-based search trends for symptoms associated with COVID-19 coincided with the disease outbreak [14]. Conversly, the global web-based interest in information on HIV/AIDS care services decreased [15]. However, the search engine trend for HIV/AIDS testing during the COVID-19 pandemic has not been explored extensively in the Japanese population.…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported a significant positive correlation between Google Trends search data and confirmed, suspected and probable cases. Ornos et al [41] showed that HIV search volume was positively correlated with the disease prevalence and negatively correlated with GDP and the number of doctors. This result demonstrated the need to improve the quality of HIV-related health information to improve health-seeking behaviors in countries with higher HIV infection rates.…”
Section: Applications Of Infodemi-ology In Diseases 41 Infectious Dis...mentioning
confidence: 99%